National or Global? Moderated Mediation Impact of Sports Celebrity Credibility on Consumer’s Purchase Intention - Dikčius, Vytautas; Ilciukiene, Svetlana (Organizations and Markets in Emerging Economies, 2021)
The paper aims to examine the role of localness of a sports celebrity and a level of product involvement in the mediated impact of the perceived product quality on the relationship between a sports celebrity’s credibility and consumers’ purchase intention in a developing economy. A total of 253 respondents participated in an experiment including the localness of 2 sports celebrities (global vs national) and2 product involvement (high vs low) levels. The study determined that sports celebrity credibility had both direct and indirect effects on respondents’ intention to buy, but product involvement moderated the direct impact of sports celebrity credibility on the consumer’s intention to buy a product. The direct impact was noticed in the case of low involvement products, and no impact was observed in the situation of high involvement. Besides, the study showed that global sports celebrities enjoyed a higher level of attractiveness, but the trustworthiness was higher for national celebrities. Finally, moderation analysis showed that the mediation effect of the localness of a sports celebrity on the relationship between credibility and intention to purchase depended on the type of measured effect – direct or indirect. This study expands the research on the effects of celebrity credibility on the consumer’s intention to purchase in developing economies.
Keywords: sports celebrity; source credibility; product involvement; perceived quality; consumer’s purchase intention; moderating mediation; globalisation